Successful Balanced Gait after Reconstruction of the Weight-bearing Mid Plantar Region Using a Free Contralateral Medial Plantar Flap. Issue 9 (September 2019) - Karakawa, Ryo; Yoshimatsu, Hidehiko; Miyashita, Hiroki; Kuramoto, Yukiko; Shibata, Tomoyoshi; Yano, Tomoyuki
Abstract : Summary: Although soft tissue sarcoma, especially in the sole of the foot, is a rare disease, weight-bearing region reconstruction considering postoperative gait is needed. For functionally satisfactory sole reconstruction, it is important to cover the weight-bearing region with a nonbulky but durable skin paddle that can withstand a significant amount of shear pressure. We herein present a case in which a free contralateral medial plantar flap was used for reconstruction of the weight-bearing mid plantar region for a 41-year-old man who suffered from mid-foot sarcoma. Gait analysis was performed 6 months after the operation with the lower limb loading gauge sheet, and the result indicated that postoperative balanced gait was obtained. The free medial plantar flap transfer after sole sarcoma resection has several advantages. First, the characteristic of this flap with solid anchoring to deep tissue to resist shearing makes it possible to lower the chances of postoperative ulceration. Second, the medial plantar flap has optimal thickness and good color and texture match for sole reconstruction. Third, a sensate flap can be achieved if the medial plantar nerve is included. Although further clinical investigations such as long-term follow-up will be required to confirm its efficacy, this method would be one option for treating sole sarcoma.